Discipline "Design of advertisement" in the Art pedagogical education - V.V. Tomashevskiy (Academy of Cognitive and Natural Sciences, 2009)
In article Is considered the questions of the role and place of the disciplines "Design of advertisement" in the learning process of the art-graphic department of Kriviy Rig pedagogical university.